La lexicografia catalana a l'Alguer - Corbera, Jaume (Caplletra. Revista Internacional de Filologia, 2015)
The re are a few alguerès works made with lexicographic methods or pretensions, apart from some contributions more or less interesting or useful for the knowledge of the local language, intended principally for dialectologists: only two titles produce explicitly the label of «Vocabulary» or «Dictionary» and use the typical structure of this kind of works. We can add to these references an unpublished work by G. Palomba.